Reliability of the Thai version of the modified STarT Back Screening Tool in individuals with neck pain - Phungwattanakul, Nattawan; Boonyapo, Uchukarn; Wiangkham, Taweewat (Chulalongkorn Medical Journal, 2022)
Backgrounds: The modified STarT Back Screening Tool in Thai version (mSBST-TH) for individuals with neck pain (NP) was adapted from the STarT Back Screening Tool in Thai version (SBST-TH) for individuals with low back pain (LBP) to classify individuals with NP into low, medium, and high risk for chronicity. Owing to a lot of individuals with NP in Thailand. It would be beneficial if the mSBST-TH was available to help primary care management in Thai individuals with NP. However, the reliability of this tool has not been investigated. Objective: The aim of this cross-sectional study was to investigate the reliability of the mSBST-TH for individuals with NP. Methods: A total of 261 subjects (aged 20 - 70 years) with NP in Phitsanulok Province completed the mSBST-TH for evaluating the internal consistency. The test-retest reliability was assessed by 50 subjects who completed the mSBST-TH twice, with an interval of two days. Results: The test-retest reliability of the mSBST-TH was 0.81 (95% confidence interval [CI]: 0.69 - 0.88) for the total score and 0.70 (95% CI, 0.53 - 0.82) for the psychosocial subscore. The internal consistency was 0.73 for the total score (range 0.68 - 0.74). The standard error of measurement (SEM) was 0.564 (total score) and 0.559 (psychosocial subscore). Lastly, the minimal detectable change of the mSBST-TH total score was 1.563. Conclusion: The mSBST-TH is a reliable tool to classify individuals with NP, with acceptable test-retest reliability and internal consistency.